If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x) + -4 = 5 + -1x Reorder the terms: -4 + 2x = 5 + -1x Solving -4 + 2x = 5 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -4 + 2x + x = 5 + -1x + x Combine like terms: 2x + x = 3x -4 + 3x = 5 + -1x + x Combine like terms: -1x + x = 0 -4 + 3x = 5 + 0 -4 + 3x = 5 Add '4' to each side of the equation. -4 + 4 + 3x = 5 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 5 + 4 3x = 5 + 4 Combine like terms: 5 + 4 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 8+4(z-2)=-5z+5 | | X^2(X^2-16)-64(X^2-16)=0 | | (1/4^2)-(3/2)-(7/4) | | x(3+7)-5=5(x+4)+5 | | y=8/3*1+8 | | 3r^2-5r-2= | | 1/4^2-3/2-7/4 | | n/7+6=13 | | 4=3x-8-2(5-x) | | t^4+43t^2+42=0 | | r^2-3r+2= | | 3c-12=145c | | 3k^2+-14k+8= | | 3m^2-8m=0 | | -1.6(1+7.6r)=-90.368 | | -7/3=-7/2u-7/5 | | 3(-6+x)=4x-1/3 | | (3x+7/4)+(x+22/5)=9 | | -8*1+7y=-56 | | 5(3m+8)+8(m+4)=95 | | 9d^2+18d+8=0 | | 9a-3a=2a+24 | | 3x+7/4+x+22/5=9 | | (5x-9)(2x+3)= | | t-(9)=4 | | 2x-5+7x=11-3x+4 | | 5(3m+8)+8(m+4)=63 | | (5z/2z)*(9/z) | | nb=n+a | | ((-4z^6)/5z)*(9/z) | | 14=(-p-8) | | x+6=x-7 |